Identifikasi Penyakit Tanaman Jarak Pagar Menggunakan Metode Fuzzy K-Nearest Neighbor (FK-NN) - Eva Agustina Ompusunggu; Dian Eka Ratnawati; Lailil Muflikhah (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Jatropha (Jatropha curcas L., Euphorbiaceae) is a plant that has many uses that as a raw material medicines and vegetable oil (biodiesel). Jatropha is used to cure various diseases. Some people also make Jatropha as a main ingredient of their livelihoods. However, the quality of Jatropha decreased due to various diseases. Lack of knowledge about the disease of jatropha and do not know how to overcome it became one of the causes. As well as the unavailability of media for the public to know the diseases that attack. To know and make it easier to diagnose diseases that attack jatropha, a system needs to be made. To support this diagnosis used k-nearest neighbor and fuzzy method. The first step of this method is entering training data that contains symptoms. Then classification using the k-nearest neighbor and fuzzy. Then we get the result of this system which is the diagnosis of Jatropha's diseases from nine diseases that there are. Results of tests performed on this study, obtained the highest accuracy by 80%